A common ground switched capacitor‐based single‐phase five‐level transformerless inverter for photovoltaic application - Singh Neti, Sukhdev; Singh, Varsha (International journal of circuit theory and applications, 2023)
Summary Transformerless inverters (TLI) are widely accepted in photovoltaic (PV) systems. With the application of TLI, the bulky transformer from the conventional system can be removed, enhancing the PV system's compactness, cost, and efficiency. The direct connection of PV to the grid through the TLI causes common mode voltage (CMV). The variation of CMV causes the leakage current (LC) in the TLI topology. This paper suggests a new topology of five‐level TLI for the PV system. The problem of LC is mitigated by providing common ground (CG) for both PV and the grid neutral. This topology uses only five switches, a diode, two DC link capacitors, and a switched capacitor (SC) to produce the five‐level output voltage. Only two switches are conducted for positive and negative voltage level generation. The charging current of the SC is limited by using the front‐end inductor. A level‐shifted pulse width modulation (LS‐PWM) is adopted for generating the gate pulses. A detailed mathematical approach has been suggested for the component selection and the losses associated with it through theoretical calculation and simulation. Further, an explicit comparative study is performed with existing similar kinds of topologies to claim the merits of the proposed topology. This topology is validated using both MATLAB/Simulink and the laboratory prototype model for a 1 kW system. It is observed that the voltage stress and current stress across the component are very less. Overall, the component count is reduced and helps to get an enhanced efficiency of 96.7%. This topology uses five switches, a diode, two DC link capacitors, and a switched capacitor (SC) to obtain the output voltage. The SC is self‐balanced, by properly charging and discharging. A new bidirectional switch B‐TRANS IPBD1205A4ES is used to improve the efficiency of the topology. Both photovoltaic (PV) and grid neutral are commonly grounded as shown in the graphical . The proposed topology has a common ground structure along with the flow of leakage current through the parasitic capacitance but zero leakage current.